Stock Split : Examination to Signaling on Indonesia Stock Exchange 2017-2019 - Abdul Hafiz Tanjung; Helma Yunia Putri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
The purpose of this research is to provide empirical evidence for signaling theory in the companies that conducted stock splits on Indonesia Stock Exchange between 2017 and 2019. This research examined the profit growth of companies that do and do not stock splits in period before stock split. Non-parametric statistics, the Mann-Whitney U test were utilized in the statistical analysis. Normality test were previously used to determine the statistical analysis that would be utilized. This research used a sample size of 28 companies that splitting their stock and 86 companies that do not split their stock. The research found that profit growth differences in the year 2017, 2018, 2019 and pool data from 2017 to 2019 are signaling.